Materials, Design and Process Development for Additive Manufacturing - Sufiiarov, Vadim (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Additive manufacturing is already actively used in various high-tech industries today. At the same time, there is a certain limitation and imperfection of known and widely used conventional materials when they are used in additive manufacturing. In this regard, extensive research and development are aimed at the advancements of new materials by adjusting the chemical compositions of conventional alloys, new equipment with expanded functionality and the ability to work with a wide range of materials that were previously not available for additive manufacturing. This Special Issue covers a wide scope of additive manufacturing processes, comprising investigation, characterization of materials and their properties, development and application of new materials, structures designed for additive manufacturing, as well as processes and techniques that will expand the potential applications of layer-by-layer synthesis.